Methotrimeprazine versus haloperidol in palliative care patients with cancer-related nausea: a randomised, double-blind controlled trial. Issue 9 (12th September 2019) - Hardy, Janet Rea; Skerman, Helen; Philip, Jennifer; Good, Phillip; Currow, David C; Mitchell, Geoffrey; Yates, Patsy
Abstract : Objectives: Methotrimeprazine is commonly used for the management of nausea but never tested formally against other drugs used in this setting. The aim was to demonstrate superior antiemetic efficacy. Design: Double-blind, randomised, controlled trial of methotrimeprazine versus haloperidol. Setting: 11 palliative care sites in Australia. Participants: Participants were >18 years, had cancer, an average nausea score of ≥3/10 and able to tolerate oral medications. Ineligible patients had acute nausea related to treatment, nausea for which a specific antiemetic was indicated, were about to undergo a procedure or had received either of the study drugs or a change in glucocorticoid dose within the previous 48 hours. Interventions: Based on previous studies, haloperidol was used as the control. Participants were randomised to encapsulated methotrimeprazine 6·25 mg or haloperidol 1·5 mg one time or two times per day and assessed every 24 hours for 72 hours. Main outcome measures: A ≥two-point reduction in nausea score at 72 hours from baseline. Secondary outcome measures were as follows: complete response at 72 hours (end nausea score less than 3), response at 24 and 48 hours, vomiting episodes, use of rescue antiemetics, harms and global impression of change. Results: Response to treatment at 72 hours was 75% (44/59) in the haloperidol (H) arm and 63% (36/57) in the methotrimeprazine (M) arm with no difference between groups (intention-to-treat analysis). Complete response rates were 56% (H) and 51% (M). In the per protocol analysis, there was no difference in response rates: (85% (44/52) (H) and 74% (36/49) (M). Complete per protocol response rates were 64% (H) and 59% (M). Toxicity worse than baseline was minimal with a trend towards greater sedation in the methotrimeprazine arm. Conclusion: This study did not demonstrate any difference in response rate between methotrimeprazine and haloperidol in the control of nausea. Trial registration number: ACTRN 12615000177550.